A compact dual-polarized co-radiator MIMO antenna for UWB applications. Issue 2 (24th March 2022) - Kaur, Harleen; Shankar Singh, Hari; Upadhyay, Rahul
Abstract: In this research study, a compact dual-polarized co-radiator ultra-wideband (UWB) multiple-input multiple-output (MIMO) antenna with improved impedance bandwidth and isolation is proposed for wireless applications. The designed co-radiator has an overall area of 0.3 λ o × 0.3 λ o mm 2 (where, λ o is free space wavelength corresponding to the lower cut-off frequency, i.e., 3.1 GHz). The proposed resonator comprises of a hybrid geometry which is created with the combinations of a circular-shaped patch, a square, and two rectangular stubs. It is centrally aligned between two 50 Ω micro-strip feed lines that are positioned orthogonal to each other. Further, the modified ground plane is attached with the end-loaded line which provides broadband isolation over entire UWB frequency band. The simulated results of the proposed antenna exhibit wideband characteristics with impedance bandwidth of 3.1–16.9 GHz with minimum isolation of −15 dB. Moreover, all the radiation performance parameters are analyzed and discussed. Some important diversity parameters such as envelope correlation coefficient, mean effective gain, effective diversity gain, and channel capacity loss have also been evaluated. Furthermore, all the measured results of proposed antenna agree well with the simulated results which make the proposed antenna a suitable candidate for UWB-MIMO wireless applications.